Peningkatan Menulis Naskah Drama Melalui Model Example non Example Kelas X SMA Nurul Ilmi Padangsidempuan - Elnila Caniago; Gultom, Fita Delia (Journal Education Innovation (JEI), 2024)
This research was conducted at Nurul Ilmi Padangsidempuan Private High School in class X for the 2023-2024 academic year. The population of this research was 98 students consisting of 3 classes, while the number of samples used in this research was 34 students. The research method used in this research is classroom action research which consists of three stages, namely practicum, cycle I and cycle II. In obtaining research results, the data collection tool in research for variable Meanwhile, the assessment for variable y is writing a drama script, plot, setting, actions (actions), characterization and point of view. From the results of the research carried out, the pre-action results obtained with an average score of 62.38, after learning was carried out in cycle I, there was an increase in the average score to 70.91 and in the second cycle treatment the average score of 85, 62 students was obtained. class X Nurul Ilmi Padangsidempuan Private High School 2023-2024 Academic Year 82.63. So in testing the hypothesis it can be concluded that there is a significant increase in student learning in writing drama scripts through the example non example learning model, so it can be concluded that the hypothesis can be accepted.